Menciptakan Lingkungan Bersih dan Nyaman untuk Membentuk Karakter Mahasiswa dan Masyarakat Peduli dan Inovatif : Pengabdian - Mochamad Saleh; Achmad Firman Rohmatulloh; Bambang Triono; Moh. Saiful Anwar; Terubus Terubus (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Environmental problems such as low public awareness of cleanliness, increasing waste volume, and ecosystem degradation remain serious challenges in urban areas. These conditions directly affect environmental quality, public health, and community comfort. This article aims to describe the implementation of a community service program through environmental clean up activities to create a clean and comfortable environment while shaping caring and innovative character among students and local communities. The method applied was Participatory Action Research (PAR) involving students, community members, and related institutions from planning, implementation, to evaluation stages. Activities were conducted in the Afvoer Kemambang River area and the Universitas Sunan Giri Surabaya campus through collective actions cleaning waste, weeds, and tree branches. The results show significant improvement in environmental cleanliness, growth of collective awareness, and behavioral changes in waste management practices. Furthermore, the program strengthened collaboration between universities, government agencies, and communities and encouraged sustainable initiatives such as rotating cleanliness schedules.